Research on Networked Traction Power Supply System and Its Optimal Dispatching Strategy - LI Hongbo; XU Dongsheng; HUANG Zhihao; YIN Xiaowei; ZHANG Min; WANG Xiong; ZHANG Zhixue (Kongzhi Yu Xinxi Jishu)
Train regenerative braking energy accounts about 10%~30% of the total traction energy, and its efficient utilization is of great importance to building green and low-carbon railway traction power supply system. Traditional railway traction power supply system consists of multiple independent sections, and energy cannot be transferred between sections. This restricts the utilization of regenerative energy in the traction power supply system. To solve this problem, this paper proposes a networked traction power supply system, where energy dispatching equipment is installed in the section post to connect adjacent sections. Topology of the networked traction power supply system and principles of the energy dispatching equipment are introduced in this paper, and energy dispatching equipment group's optimal strategy aimed for cost reduction is proposed too. The simulation result shows that compared with the traditional traction power supply system, the forward energy of networked traction power supply system can be reduced by 17.3%, and the maximum power of substation can be reduced by about 19.0%. The correctness and effectiveness of the networked traction power supply system's working principle and dispatching strategy are verified.